2017
DOI: 10.4209/aaqr.2016.07.0304
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory-Based Models and Remote Sensing for Biomass Burning Assessment in Bangladesh

Abstract: Biomass burning is a major global source of fine primary carbonaceous particles including strongly light absorbing compounds and marker compounds. In a prior study, particulate matter (PM) sampling was conducted during 2010-2012 period at sites in Rajshahi, Dhaka, Khulna, and Chittagong. PM samples were collected using dichotomous samplers in the PM 2.5 and PM 2.5-10 size fractions. The samples were analyzed for mass, black carbon at 370 nm (UVBC) and 880 nm (BC), Delta-C (UVBC-BC), and elemental compositions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Transported pollutants at any site may also increase the load of contaminants, and the source-apportionment studies are found to be useful for finding the regions, which are responsible for transported pollution to any location (e.g. [25,40]). This situation, however, may be different at coastal stations during the winter season, where land-sea breeze interacts with the atmospheric boundary layer variation, and pollutants concentrations are changing during diurnal cycle (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Transported pollutants at any site may also increase the load of contaminants, and the source-apportionment studies are found to be useful for finding the regions, which are responsible for transported pollution to any location (e.g. [25,40]). This situation, however, may be different at coastal stations during the winter season, where land-sea breeze interacts with the atmospheric boundary layer variation, and pollutants concentrations are changing during diurnal cycle (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…During the winter season brick kilns start their production which contributes to total air pollution with the other sources in Dhaka city [29]. The evidence also showed that high concentration of PM during the winter season is caused by the seasonal fluctuations and transportation of the pollutants from the north and northwesterly directions of air [30,31] that also indicates the PM concentration is influenced by transboundary emission, especially in winter season [30].…”
Section: Seasonal Variation Of Particulate Mattermentioning
confidence: 99%
“…Detailed information regarding the trajectory model and these data sets can be found on the NOAA Web site (http://www.arl.noaa.gov/re ady/hysplit4.html). This type of analysis has been widely applied in the environmental sciences; for instances, to investigate the long-range transport of pollutants and to establish the source-receptor relationships of air pollutants (Stohl, 1998;Xin et al, 2016;Ommi et al, 2017;Yang et al, 2017). Different air masses travel through different regions and therefore bring different chemical constituents with them, leading to different air quality characteristics in downwind areas (Abdalmogith and Harrison, 2005;Wang et al, 2006b;Kong et al, 2010).…”
Section: Backward Trajectory Analysismentioning
confidence: 99%